CT Radiomics Model for Predicting the Ki-67 Index of Lung Cancer： An Exploratory Study - Fu, Qing; Liu, Shun li; Hao, Da peng; Hu, Ya bin; Liu, Xue jun; Zhang, Zaixian; Wang, Wen hong; Tang, Xiao yan; Zhang, Chuan yu; Liu, Shi he (Frontiers in Oncology, 2021)
Objective To establish a radiomics signature and a nomogram model based on enhanced CT images to predict the Ki-67 index of lung cancer. Methods From January 2014 to December 2018, 282 patients with lung cancer who had undergone enhanced CT scans and Ki-67 examination within 2 weeks were retrospectively enrolled and analyzed. The clinical data of the patients were collected, such as age, sex, smoking history, maximum tumor diameter and serum tumor markers. Our primary cohort was randomly divided into a training group (n=197) and a validation group (n=85) at a 7:3 ratio. A Ki-67 index ≤ 40% indicated low expression, and a Ki-67 index > 40% indicated high expression. In total, 396 radiomics features were extracted using AK software. Feature reduction and selection were performed using the lasso regression model. Logistic regression analysis was used to establish a multivariate predictive model to identify high and low Ki-67 expression in lung cancer. A nomogram integrating the radiomics score was established based on multiple logistic regression analysis.Area under the curve（AUC）was used to evaluate the prediction efficiency of the radiomics signature and nomogram. Results The AUC,sensitivity, specificity and accuracy of the radiomics signature in the training and validation groups were 0.88 (95% CI: 0.82~0.93) ,79.2%,84.3%,81.2% and 0.86 (95% CI: 0.78~0.94),74.6%,88.1%,79.8%, respectively. A nomogram combining radiomics features and clinical risk factors (smoking history and NSE) was developed. The AUC, sensitivity, specificity and accuracy were 0.87 (95% CI: 0.80~0.95), 75.0%, 90.2% and 83.5% in the validation group, respectively. Conclusion The radiomics signature and nomogram based on enhanced CT images provide a way to predict the Ki-67 expression level in lung cancer.